P411 MINOCA OR NOT MINOCA? THE DECISIVE ROLE OF CARDIAC MAGNETIC RESONANCE IN THE DIFFERENTIAL DIAGNOSIS OF MYOCARDIAL DAMAGE. (18th May 2022) - Dal Passo, B; Cardelli, L; Perugini, E; Bugani, G; Canovi, L; Frascaro, F; Zanarelli, L; Piscitelli, L; Colletta, M; Casella, G
Abstract: Cardiac MRI can facilitate the differential diagnosis of myocardial damage in patients without coronary artery disease. Our case report is about a 50–year–old man who was admitted to the Emergency Department of the Maggiore Hospital in Bologna in October 2021 for oppressive chest pain at rest; previously he had experienced a similar episode but of minor intensity. He had not previous medical records. When the patient arrived at the emergency department chest pain had regressed, blood pressure was elevated (170/110 mmHg). The ECG showed sinus tachycardia at 100 bpm without electrocardiographic abnormalities suggestive of acute ischemia. Cardiac biomarkers were elevated (hsTnI 312 ng / L –> 975 ng / L – n.v. <19.8 ng / L); blood gas analysis showed pH 7.42, pO2 47 mmHg and pCO2 33 mmHg. Chest CT scan excluded pulmonary embolism and acute aortic syndrome. The patient was transferred to Cardiology Ward in the suspicion of acute coronary syndrome, where echocardiogram showed normal biventricular volumes, mild wall hypertrophy and hypokinesia of the lower middle wall (EF 52%). Coronary angiography didn't showed any obstructive stenosis in any epicardial vessels. In consideration of the clinical presentation and instrumental evidences, the patient was discharged with a diagnosis of myocardial infarction with non–obstructive coronary arteries (MINOCA), but a cardiac MRI was scheduled in the post–discharge to clarify its genesis. MRI didn't showed any areas of signal hyperintensity, any perfusion deficits in the first pass study and any areas of late gadolinium enhancement (LGE). Those images permitted to exclude areas of necrosis or inflammation, orienting the diagnosis to myocardial damage during hypertensive crisis. Therefore, the antiplatelet therapy recommended at discharge was suspended. In this case report, cardiac magnetic resonance showed that it can improve the etiological diagnosis of MINOCA, allowing for better clinical and therapeutic management.